2010
DOI: 10.1007/s10853-010-5168-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable, mesoporous mixed lanthanum–cerium oxides with tailored structure and reducibility

Abstract: Pure and mixed lanthanum and cerium oxides were synthesized via a reverse microemulsion-templated route. This approach yields highly homogeneous and phase-stable mixed oxides with high surface areas across the entire range of La:Ce ratios from pure lanthana to pure ceria. Surprisingly, all mixed oxides show the fluorite crystal structure of ceria, even for 10 lanthanum contents as high as 90%. Varying the La:Ce ratio not only allows tailoring of the oxide morphology (lattice parameter, pore structure, particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 55 publications
8
26
0
Order By: Relevance
“…Between the two regions, the signal falls below baseline (arrow in Figure ), and this implies that H 2 was physically adsorbed in the first region and released in the 600–700 °C temperature range, which is in agreement with the results of Bruce et al Similar reduction profiles were found for ceria with low La content (up to 5 atom‐%), as shown in Figure . H 2 uptake decreases for promoted samples, due to lattice replacement of Ce 4+ ions by nonreducible La 3+ ions, as was concluded by previous XRD analysis and in agreement with the literature . CeLa50 is an exception; it does not follow said trend.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Between the two regions, the signal falls below baseline (arrow in Figure ), and this implies that H 2 was physically adsorbed in the first region and released in the 600–700 °C temperature range, which is in agreement with the results of Bruce et al Similar reduction profiles were found for ceria with low La content (up to 5 atom‐%), as shown in Figure . H 2 uptake decreases for promoted samples, due to lattice replacement of Ce 4+ ions by nonreducible La 3+ ions, as was concluded by previous XRD analysis and in agreement with the literature . CeLa50 is an exception; it does not follow said trend.…”
Section: Resultssupporting
confidence: 90%
“…An even larger difference between bulk and superficial concentration is found in the case of CeLa50. Other authors have also reported this same feature for mesoporous CeLa materials synthesized by the reverse microemulsion method …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…It is a new reduction temperature and remarkably relative to that of pure CeO 2 nanorods. In comparison with the reference, due to the synergist interaction between La–O and Ce–O, the reduction temperature of Ce-La nanorods was higher than pure CeO 2 [31, 54]. It could be found that the binary oxides should have independent CeO 2 and LaO x .…”
Section: Resultsmentioning
confidence: 85%
“…In comparison to La-incorporated HfO 2 , the La-incorporated CeO 2 shows better HK properties. This can be attributed to the fact that Ce and La have similar atomic and chemical properties, 25 thus allowing a ready intermixing of the two species in the stack.…”
Section: Figures 1(a) and 1(b) Show Transmission Electron Microscopy mentioning
confidence: 99%